MITOS KECANTIKAN TUBUH WANITA PADA KAKAWIN SMARA TANTRA - Putu Eka Sura Adnyana; Ni Made Yuliarmini; Widya Duta (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
The concept of beauty attached to a woman's body does not onlyoccur in the real world but also in literary works. Beauty myths forminterpretations to women in the analyzed Smara Tantra kakawin. Beautymyths intimidate women in such a systematic and organized way. As longas women think that being beautiful according to the representation ofsociety's glasses is an absolute necessity. Kakawin Smara Tantra, which isquite famous among Balinese people, only sees from the point of view ofmen the beautiful construction of women. Beauty myths created inkakawin Smara Tantra have shackled women so that women no longerrespect themselves and only focus on physical form. Although the truebeauty of women is not only radiated from the physical but must bebalanced with beauty that comes from within (inner beauty).